IlluminationCut - Bus, N.; Mustafa, N. H.; Biri, V. (Computer graphics forum, 2015)
We present a novel algorithm, IlluminationCut, for rendering images using the many‐lights framework. It handles any light source that can be approximated with virtual point lights (VPLs) as well as highly glossy materials. The algorithm extends the Multidimensional Lightcuts technique by effectively creating an illumination‐aware clustering of the product‐space of the set of points to be shaded and the set of VPLs. Additionally, the number of visibility queries for each product‐space cluster is reduced by using an adaptive sampling technique. Our framework is flexible and achieves around 3 – 6 times speedup over previous state‐of‐the‐art methods.